Semi-artificial photobiocatalysis via genetically modified sulfur metabolism to in situ assembly of a solar-biohybrid for antibiotic degradation - Shuhan Dai; Lei Niu; Yiran Lv; Haoran Zhang; Li Xu; Yuan Liao; Xiping Hu; Xiaoman Xie; Jinyong Yan; Yunjun Yan (Bioresource Technology, 2026)

Bioinspired ordered FeCo/biomass-derived carbon aerogels for broadband microwave absorption and multifunctional thermal-mechanical integration - Xiaoke Tian; Kun Wang; Huanhuan Li; Houjin Zhang; Xiaoman Xie; Min Yang; Yunjun Yan (Chemical Engineering Journal, 2026)

Construction of self-sustaining dual regeneration system through co-immobilized multienzyme and cofactor for sustainable 13-hydroxyoctadecadienoic acid synthesis - Xiaoxiao Liu; Kai Li; Pengbo Wang; Kung Wang; Shuhan Dai; Xiaoman Xie; Min Yang; Li Xu; Yunjun Yan; Jinyong Yan (Bioresource Technology, 2026)

A novel bioengineered strategy for efficient heavy metals remediation: Harnessing alkaline phosphatase-displaying E. coli to enhance microbial-induced phosphate precipitation - Zhen Zheng; Xiaoman Xie; Xinyi Hu; Wanlin Zheng; Shuhan Dai; Jianping Liu; Jinyong Yan; Min Yang; Yunjun Yan; Li Xu (Bioresource Technology, 2026)

Mussel-inspired bioadhesive via enzymatic adhesive peptide synthesis and liquid-liquid phase separation for robust adhesion in harsh environments - Siqiang Wang; Kai Li; Zitang Xu; Hao Wang; Qiyang Wang; Ao Lin; Pengbo Wang; Xiaoman Xie; Li Xu; Yunjun Yan (Chemical Engineering Journal, 2026)

Harnessing CO2 for sustainable bioelectricity: An engineered two-stage microbial co-culture approach with enhanced acetate metabolism - Xiaoman Xie; Ying Wu; Yiran Lv; Shuhan Dai; Huanhuan Li; Li Xu; Min Yang; Jinyong Yan; Yunjun Yan (Bioresource Technology, 2025)

The impact of enclosure management on the conservation and restoration of microbial community in a typical urban lake - Hanhui Huang; Kangxin Xiao; Tianqiao Shen; Dongliang Chu; Zhicai Xie; Yonghong Bi; Kang Ning; Yunjun Yan (Science of The Total Environment, 2025)

The study of the response regularity of photosynthesis to flash drought in different vegetation ecosystems of the middle and lower reaches of the Yangtze River Basin - Yunjun Zhan; Chuanqi Ma; Yan Yan; Yongsi Luo; Xueting Wang; Senrong Wang; Yuejing Rong (International Journal of Biometeorology, 2025)

Design and biofabrication of barnacle and spider silk protein decorated composite bacterial cellulose for diabetic wound healing - Luona Ye; Yunjun Yan; Jinyong Yan (Carbohydrate Polymers, 2025)

Systemic inflammatory response to daily exposure to microcystin-LR and the underlying gut microbial mechanisms - Yanyan Zhao; Harry Sokol; Qing Cao; Hui Zhang; Yunjun Yan; Liqiang Xie; Haotian Wang (Journal of Hazardous Materials, 2024)

In-situ co-immobilization of lipase, lipoxygenase and L-cysteine within a metal-amino acid framework for conversion of soybean oil into higher-value products - Xiaoxiao Liu; Kai Li; Luona Ye; Xinghong Cao; Pengbo Wang; Xiaoman Xie; Min Yang; Li Xu; Yunjun Yan; Jinyong Yan (Food Chemistry, 2024)

Modification of Yarrowia lipolytica via metabolic engineering for effective remediation of heavy metals from wastewater - Kaixin Yang; Guowei Zhao; Huanhuan Li; Xiaoke Tian; Li Xu; Jinyong Yan; Xiaoman Xie; Yunjun Yan; Min Yang (Journal of Hazardous Materials, 2024)

Effective removal of phenol from polluted water via bio-based rigid polyurethane foams in collaboration with Alcaligenes faecalis - Guangxu Bo; Liangcheng Jiao; Huanhuan Li; Guowei Zhao; Zitang Xu; Xiaoxiao Liu; Pengbo Wang; Xiaoke Tian; Jinyong Yan; Xueqing Wang; Yunjun Yan (Journal of Water Process Engineering, 2023)

A novel strategy for reinforcing cementation process coupling microbially induced carbonate precipitation (MICP) with cross-linked silk fibroin - Zhaorui Gu; Xiaojing Li; Jiao Wu; Shuang Niu; Pengbo Wang; Jun-Jie Zheng; Jinyong Yan; Li Xu; Min Yang; Yunjun Yan (Journal of Environmental Chemical Engineering, 2023)

Synthesis, characterization, anticancer efficacy evaluation of ruthenium(II) and iridium(III) polypyridyl complexes toward A549 cells - Lijuan Liang; Yan Yang; Haimei Liu; Fang Yuan; Yuhan Yuan; Wenlong Li; Chunxia Huang; Jing Chen; Yunjun Liu (JBIC Journal of Biological Inorganic Chemistry, 2023)

Analysis of VOC emissions and O3 control strategies in the Fenhe Plain cities, China - Yafei Liu; Peipei Qiu; Kai Xu; Chenlu Li; Shijie Yin; Yunjun Zhang; Yu Ding; Chen Zhang; Zheng Wang; Ruixiao Zhai; Yijun Deng; Fengyu Yan; et al. (Journal of Environmental Management, 2023)

Mussel foot inspired bionic adhesive material enhanced by a reconstructed in vitro system for interfacial adhesion - Kai Li; Zitang Xu; Xiaoxiao Liu; Yaojia He; Xiaoke Tian; Xiaoling Xu; Guangxu Bo; Sheng Yuan; Li Xu; Min Yang; Jinyong Yan; Houjin Zhang; et al. (Chemical Engineering Journal, 2023)

Mechanisms of niche‐neutrality balancing can drive the assembling of microbial community - Lixiao Wang; Maozhen Han; Xi Li; Bingbing Yu; Huading Wang; Amjed Ginawi; Kang Ning; Yunjun Yan (Molecular Ecology, 2021)
One hotspot of present community ecology is to uncover the mechanisms of community succession. In this study, two popular concepts, niche‐neutrality dynamic balancing and co‐occurrence network analysis, were integrated to investigate the dispersal dynamics of microbial communities in a freshwater river continuum in subtropical China. Results showed that when habitat conditions were mild and appropriate, such as in the clean upstream river, free of heavy pollution or long‐lasting extreme disturbances, stochastic processes could increase species diversities, and organize communities into relatively loosely linked and stable networks with higher modularity and more modules. However, when conditions became degraded under heavy pollution, the influence of neutrality diminished, and niche‐based selection imposed more constraints on communities and guided the assembling processes in certain directions: depleting species richness, strengthening interspecies connections and breaking boundaries of modules. Consequently, communities became more sensitive to fluctuations so as to deal with the harsh conditions efficiently. Another interesting finding was that, both as keystone taxa of communities, module hubs were mostly neutrally distributed generalists with high abundances, and were beneficial to many related operational taxonomic units. In contrast, connectors were less abundant and their distributions were more subjected to the environments. Therefore, connectors were probably responsible for the information transmission between microbial communities and environments, as well as between different modules, and thus could restrict the dispersal of microbes and guide the direction of community assembly.

Global Profiling of Alternative Splicing in Callus Induction of Immature Maize Embryo - Xuemei Du; Ting Fang; Yan Liu; Liying Huang; Xiaoli Wang; Jie Zhang; Yangbo Cui; Maosen Zang; Guoying Wang; Junjie Fu; Yunjun Liu (In Vitro Cellular & Developmental Biology - Plant, 2020)

Two alternative splicing variants of maize HKT1;1 confer salt tolerance in transgenic tobacco plants - Zhenjing Ren; Yan Liu; Dan Kang; Kaijian Fan; Cuiyun Wang; Guoying Wang; Yunjun Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Metabolic effects of glyphosate on transgenic maize expressing a G2-EPSPS gene from Pseudomonas fluorescens - Yunjun Liu; Yuwen Zhang; Yan Liu; Wei Lu; Guoying Wang (Journal of Plant Biochemistry and Biotechnology, 2015)

Assessment of transgene copy number and zygosity of transgenic maize overexpressing Cry1Ie gene with SYBR® Green qRT-PCR - Yuwen Zhang; Yan Liu; Jie Zhang; Guoying Wang; Jianhua Wang; Yunjun Liu (In Vitro Cellular & Developmental Biology - Plant, 2015)

Enhanced Performance of Rhizopus oryzae Lipase Immobilized on Hydrophobic Carriers and Its Application in Biorefinery of Rapeseed Oil Deodorizer Distillate - Feng Su; Guanlin Li; Houjin Zhang; Yunjun Yan (BioEnergy Research, 2014)

Improved Insecticidal Toxicity by Fusing Cry1Ac of Bacillus thuringiensis with Av3 of Anemonia viridis - Fu Yan; Xing Cheng; Xuezhi Ding; Ting Yao; Hanna Chen; Wenping Li; Shengbiao Hu; Ziquan Yu; Yunjun Sun; Youming Zhang; Liqiu Xia (Current Microbiology, 2014)

Overexpression of a novel Cry1Ie gene confers resistance to Cry1Ac-resistant cotton bollworm in transgenic lines of maize - Yuwen Zhang; Yunjun Liu; Yuan Ren; Yan Liu; Gemei Liang; Fuping Song; Shuxiong Bai; Jianhua Wang; Guoying Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Cloning, expression and characterization of a new lipase from Yarrowia lipolytica - Heyun Zhao; Lina Zheng; Xiaofeng Wang; Yun Liu; Li Xu; Yunjun Yan (Biotechnology Letters, 2011)

Homology modeling, molecular docking and spectra assay studies of sterol 14α-demethylase from Penicillium digitatum - Shuxiang Li; Jianhua Zhang; Shufen Cao; Rui Han; Yongze Yuan; Jiangke Yang; Yunjun Yan; Deli Liu (Biotechnology Letters, 2011)

lip2, a novel lipase gene cloned from Aspergillus niger exhibits enzymatic characteristics distinct from its previously identified family member - Jiangke Yang; Jin Sun; Yunjun Yan (Biotechnology Letters, 2010)

Cloning of a novel lipase gene, lipJ08, from Candida rugosa and expression in Pichia pastoris by codon optimization - Li Xu; Xueqing Jiang; Jiangke Yang; Yun Liu; Yunjun Yan (Biotechnology Letters, 2010)

Surface display of active lipase in Saccharomyces cerevisiae using Cwp2 as an anchor protein - Wenshan Liu; Heyun Zhao; Bin Jia; Li Xu; Yunjun Yan (Biotechnology Letters, 2010)

Temporal dynamics of production and ingestion of the dominant mayflies in a subtropical stream in China - Yunjun Yan; Xiaoyu Li (Aquatic Ecology, 2008)